Experimental Fishing in Hirakud Reservoir , Orissa (1965-67) - SULOCIIANAN, P.; GEORGE, V. C.; NAIDU, R. M. (Fishery Technology, 1968)
The comparative efficiencies of simple gill net, vertical line net and framed net in exploiting the fishery of Hirakud Reservoir in Orissa were studied. Though comparatively costlier to fabricate, the framed net gave better results than the other two.